2019
DOI: 10.1016/j.heliyon.2019.e02304
|View full text |Cite
|
Sign up to set email alerts
|

Solubility analysis of homologous series of amino acids and solvation energetics in aqueous potassium sulfate solution

Abstract: In this study we estimated the solubilities of glycine, D,L-alanine, D,L-nor-valine and D,L-serine in aqueous mixtures of potassium sulfate (K 2 SO 4 ) at 298.15 K using analytical ‘gravimetric method’. The experimental solubilities of homologous series of amino acids in aqueous K 2 SO 4 mixture were discussed in terms of relative solubility, salting-in and salting-out effect by evaluating the influential constants. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Ion effects on the relative solubility of dl -alanine in aqueous salt solutions containing the K + , Na + , and NH 4 + cations at 298.2 K. Lines are a guide to the eyes. ,,,,,, …”
Section: Results and Discussionmentioning
confidence: 99%
“…Ion effects on the relative solubility of dl -alanine in aqueous salt solutions containing the K + , Na + , and NH 4 + cations at 298.2 K. Lines are a guide to the eyes. ,,,,,, …”
Section: Results and Discussionmentioning
confidence: 99%
“…In contrast, the extractable DON concentration of Soil Q was elevated and then decreased with increases in extract salinity ( p < 0.05). Previous studies of the effects of salinity on protein solubility have shown that salting‐out effects can affect the solubility of organic matter in saline solutions, and several studies have demonstrated that these effects could even be significant at low concentrations (<0.01 M) of neutral salts (Asrami & Saien, 2018; Hossain et al, 2019). Therefore, when DON is extracted from soils using a saline solution, its solubility in the extract may also be affected by the salting‐out effect.…”
Section: Discussionmentioning
confidence: 99%
“…Dissolved amino acids, peptides, proteins, chitin, lignin, and amino sugars constitute a large proportion of DON, and each compound has specific functional groups and different relationships with the solid phase of soil (Awad et al, 2019; Quan et al, 2018; Zhang et al, 2018). Therefore, salt‐out effects can affect DON structure and induce coagulation/precipitation, which could seriously impact the DON extraction accuracy (Asrami & Saien, 2018; Hossain et al, 2019). The application of conventional extraction methods to evaluate the content of DON in unsaturated zones can be problematic.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations